Financial development and economic growth in sub-Saharan Africa: A sectoral perspective - Yazidu Ustarz; Ashenafi Beyene Fanta (Cogent Economics & Finance, 2021)
Research on the impact of financial development on economic growth remains inconclusive. Previous empirical examination of the link is based on aggregate GDP on the presumption that each economic sector responds identically to financial development. However, the extent of credit utilisation, as well as productivity of credit, may not necessarily remain the same across sectors. This study therefore seeks to contribute to the literature by examining the effect of financial development across sectors in sub-Saharan Africa using the Generalised Method of Moments (GMM) over the period 1990-2018. Indeed, the findings show that while financial development has a positive effect on the service and agricultural sectors, a certain threshold of financial development must be reached before it can positively contribute to the growth of the industrial sector. The findings are robust to a different estimation technique. With the industrial sector considered critical for economic transformation, our findings imply that policymakers in sub-Saharan Africa need to continue to promote financial development to spur industrialization.
Keywords: 330; financial development; generalised method of moments; seemingly unrelated regression; sub-Saharan Africa; threshold